Not Convinced: Lecturers' Conceptions of Quality Assurance - Sullivan, Hugh (2012)
This dissertation is an investigation into how lecturers' conceptions of quality differ from the way quality is constructed by the quality assurance systems and procedures responsible for it. Lecturers opinions about these systems are also explored. Primary research was conducted in a research intensive Irish University with a view to uncovering lecturers' views about quality assurance. This was done through semistructured interviews which were then thematically analysed and compared with a comprehensive review of the literature on quality assurance, pedagogical theory and the contemporary issues in higher education. Conclusions were drawn about the nature and value of quality assurance and the plausibility of future investigations into this area are examined.